USE OF ISOTOPE RATIOS TO ASSESS SOURCES OF PB AND ZN DISPERSED IN THE ENVIRONMENT DURING MINING AND ORE PROCESSING WITHIN THE ORLOVKA-SPOKOINOE MINING SITE (RUSSIA) - Dolgopolova A.; Weiss D.J.; Seltmann R.; Coles B.; Stanley C.J.; Mason T.F.D.; Kober B. (My University, 2006)
Element concentrations, element ratios and Pb and Zn isotope data are reported for different geologic samples (barren and ore-bearing granites and host rocks), technogenic products (ore concentrates and tailings) and biologic samples (lichens and birch leaves) from the Orlovka-Spokoinoe mining district, Eastern Transbaikalia, Russia, with the aim to trace the sources of Pb and Zn at a local level within the mining site. Lichens and birch leaves were used as receptors of contamination within the mining site. Pb/Zr and Zn/Zr values indicated Pb and Zn enrichment relative to host rocks. Zn isotope data of 15 geologic and 11 lichen samples showed different Zn isotopic signatures with the total range for the geologic suite of -0.4‰ to +1.2‰ and for lichens of +0.4‰ to +1.4‰ in δ66Zn relative to Lyon JMC Zn standard. The source of isotopically heavy Zn within the Orlovka-Spokoinoe mining site could be potentially associated with long-range atmospheric aerosols that also contributed Pb to the studied mining site. Our results demonstrated that Zn isotopes might be used as new tools for Zn source assessment. © 2006 Elsevier Ltd. All rights reserved.